Boko Haram: From local grievances to violent insurgency - Signe Marie Cold-Ravnkilde; Sine Plambech (Danish Institute for International Studies (DIIS), 2015)
This report responds to the question of how we might approach and understand the Boko Haram insurgency. In providing an answer, the report addresses three main controversies within the field of Boko Haram studies. First, whether local grievances or religious radicalisation is the main driver of the insurgency. Second, to what extent Boko Haram is mainly a local/national or regional/international group. Finally, to what extent Boko Haram and their leaders act according to a well-planned military strategy or on a more ad hoc basis. The report explores how these diverging perspectives co-exist. How to approach Boko Haram depends upon how Boko Haram and their activities are framed. Thus, a main argument of the report is that framing Boko Haram as part of a larger regional terrorist threat may mobilise support for Western military operations. If defined only as militant jihadists operating in "an arc of terrorism" it may seem as if a military response is the only right one. However, religious political violence cannot be addressed through military means alone but requires a comprehensive approach including separate socio-economic perspectives on contending incitements to engage in illicit economic activities and terrorism. Since the inauguration of a regional multinational joint task force with considerable support from international security actors in January 2015, attacks in Nigerias neighbouring countries have increased remarkably. Thus, it appears as if more international and regional military responses are contributing to the strengthening of the group. In view of this development, we want to bring forward the claim that according to the logic of retaliation that Boko Haram seems to predominately obey, there is a dynamic and mutually constitutive relationship between the way in which the Nigerian state, its neighbouring countries and the international community names and frames responses to Boko Haram, and the way in which Boko Haram operates and stages itself as a global jihadist group. Rather than rephrasing de-contextualised discourses of trans-Saharan terrorism, global jihad and international connections to Islamic State it seems more possible that the situation in north-east Nigeria is heading towards a fragmented protracted conflict with very complex social tensions. The key issues in the approach to Boko Haram are to understand and include the local dynamics of the insurgency. Therefore there is a need to pay attention in future debates and potential interventions to current military operations by Niger, Chad and Cameroon, to avoid that they repeat the same mistakes as Nigeria in 2013: human rights violations and economic sanctions that might transform a jihadist uprising into a peoples revolt. Furthermore, the report emphasises the need to include gender perspectives and the role of women within Boko Haram, and as protesters against Boko Haram, in future interventions and policymaking. Finally, strengthening of the public sectors in Nigeria and its neighbouring countries to deliver social protection to the citizens living in highly fragile environments should be supported, in order to (re)establish the social contract between state and citizens and avoid mistrust that may force some people to search out alternative forms of protection from radical jihadist groups.
Keywords: 300